1997
DOI: 10.3758/bf03199051
|View full text |Cite
|
Sign up to set email alerts
|

Choice, delay, probability, and conditioned reinforcement

Abstract: The hyperbolic-decay model is a mathematical expression of the relation between delay and reinforcer value. The model has been used to predict choices in discrete-trial experiments on delay-amount tradeoffs, on preference for variable over fixed delays, and on probabilistic reinforcement. Experiments manipulating the presence or absence of conditioned reinforcers on trials that end without primary reinforcement have provided evidence that the hyperbolic-decay model actually predicts the strength of conditioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(160 citation statements)
references
References 59 publications
(81 reference statements)
7
150
1
2
Order By: Relevance
“…Many experimental and theoretical papers on conditioned reinforcement in pigeons and rats have been published since the early 1960s using some version of the concurrent chains procedure of Autor (1960Autor ( , 1969. These studies have demonstrated a number of functional relations between rate measures and have led to several closely related theoretical proposals such as a version of the matching law, incentive theory, delay-reduction theory, and hyperbolic value-addition (e.g., Fantino 1969a,b;Grace 1994;Herrnstein 1964;Killeen 1982;Killeen & Fantino 1990;Mazur 1997Mazur , 2001Williams 1988Williams , 1994Williams , 1997. Nevertheless, there is as yet no theoretical consensus on how best to describe choice between sources of conditioned reinforcement, and no one has proposed an integrated theoretical account of simple chain and concurrent chain schedules.…”
Section: Concurrent-chain Schedulesmentioning
confidence: 99%
“…Many experimental and theoretical papers on conditioned reinforcement in pigeons and rats have been published since the early 1960s using some version of the concurrent chains procedure of Autor (1960Autor ( , 1969. These studies have demonstrated a number of functional relations between rate measures and have led to several closely related theoretical proposals such as a version of the matching law, incentive theory, delay-reduction theory, and hyperbolic value-addition (e.g., Fantino 1969a,b;Grace 1994;Herrnstein 1964;Killeen 1982;Killeen & Fantino 1990;Mazur 1997Mazur , 2001Williams 1988Williams , 1994Williams , 1997. Nevertheless, there is as yet no theoretical consensus on how best to describe choice between sources of conditioned reinforcement, and no one has proposed an integrated theoretical account of simple chain and concurrent chain schedules.…”
Section: Concurrent-chain Schedulesmentioning
confidence: 99%
“…Both the left and right stimulus lights shut off at the onset of the terminal link, which was segmented by tones in the first and last 2 s of terminal links greater than FT 6 s; a tone occurred in the first 2 s of FT 2-and 4-s terminal links. The tone segmented the delay because stimuli of longer duration may be less efficacious conditioned reinforcers [36]. The frequency of the tone (1 or 15 kHz, 75 dB) signaled the reinforcer magnitude.…”
Section: Behavioral Proceduresmentioning
confidence: 99%
“…If future choices of smaller-sooner vs. larger-later alternatives were bundled with present choices--e.g., if the choice of whether to get drunk now at the expense of feeling good tomorrow entailed committing to the same alternative for every day for the next week--the total value of the larger-later bundle relative to the smaller sooner bundle would increase, since the discounted value of the larger-later alternative in each future choice is greater than that of the smaller-sooner. Assuming that the discounted value of series of rewards is additive (as appears to be the case; Mazur, 1997), then bundling future identical choices with a current choice can reduce impulsive choice, given hyperbolic delay discounting but not exponential delay discounting (Figure 2a and 2b). 1 Experiments with both human and rodent subjects confirm a greater tolerance for delay with bundled rewards.…”
Section: Beyond Precommitment: Choice Bundling As the Basis Of Self-cmentioning
confidence: 99%